2018
DOI: 10.1097/pec.0000000000000887
|View full text |Cite
|
Sign up to set email alerts
|

Using Pleth Variability as a Triage Tool for Children With Obstructive Airway Disease in a Pediatric Emergency Department

Abstract: Our results suggest that PVI may be a useful tool in the triage of children who present to the ED with obstructive airway disease. Further studies should aim to assess the validity of PVI in predicting the response to bronchodilator therapy during the course of a patient's hospitalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Brandwein et al 16 found a significant difference in the degree of PP between children discharged home versus children admitted to the hospital. They studied the Pleth Variability Index, which is a ratio of the calculated difference in maximum and minimum amplitude of the plethysmograph waveform and the maximum amplitude 16. Though our study did not evaluate the exact degree of PP, we had similar findings of a higher RR of getting admitted to HDU/ICU among those detected to have PP on the plethysmograph after initial management.…”
Section: Discussionmentioning
confidence: 98%
“…Brandwein et al 16 found a significant difference in the degree of PP between children discharged home versus children admitted to the hospital. They studied the Pleth Variability Index, which is a ratio of the calculated difference in maximum and minimum amplitude of the plethysmograph waveform and the maximum amplitude 16. Though our study did not evaluate the exact degree of PP, we had similar findings of a higher RR of getting admitted to HDU/ICU among those detected to have PP on the plethysmograph after initial management.…”
Section: Discussionmentioning
confidence: 98%
“…Future research on these studies can enhance the understanding of these parameters, the monitoring domains, and the relations to clinical asthma outcomes. On the other hand, some hospital-based studies may provide new diagnostic opportunities such as bioimpedance [412], airway resistance during tidal breathing [413], forced oscillation technique [414], exhaled breath profiles and temperatures [415], diaphragm electromyography [416], and plethysmography variability [417][418][419]. Future research is needed to specifically review which hospital-based monitoring technologies may be beneficial for the home assessment of pediatric asthma.…”
Section: Future Perspectivesmentioning
confidence: 99%